Voltammetric sensor based on magnetic particles modified composite electrode for determination of triamterene in biological sample - Hudari, Felipe Fantinato [UNESP]; da Silva, Bianca Ferreira [UNESP]; Pividori, Maria Isabel; Zanoni, Maria Valnice Boldrin [UNESP] (Springer Nature, 2016)
Some diuretic substances are controlled and monitored by the World Anti-Doping Agency as prohibited substances for use by athletes, such as triamterene (TRT). Thus, this work describes a voltammetric method based on graphite-epoxy composite electrode modified by tosyl-functionalized magnetic particles (GECE/MPs-To) for determination of TRT diuretic in urine sample. The TRT presented an oxidation peak at +1.24 V at GECE/MPs-To with irreversible behavior. Controlled potential electrolysis of the TRT at +1.26 V indicated the two electrons are transferred during amine group oxidation and the main product was identified by LC-MS/MS. The anodic peak current is 25 % higher at the modified electrode, suggesting that TRT is adsorbed on the magnetic particles. Using optimized conditions by using multivariate optimization of the parameters inherent of the square wave voltammetry, a calibration curve was constructed with a linear relationship for TRT from 0.500 to 99.8 μmol L−1. The limits of detection and quantification were 1.47 and 4.91 × 10−7 mol L−1, respectively. The proposed method was applied to urine sample and validated by LC-MS/MS technique where the values found and compared between the two techniques showed no significant difference at 95 % confidence.
Keywords: Diuretic; Graphite-epoxy composite electrode; Magnetic particles; Multivariate optimization; Triamterene; Voltammetric sensor